Exploring Health Advice Adoption in Digital Spaces: A Dual-Theory Approach - Michael Mncedisi Willie (Universitas Negeri Surabaya or The State University of Surabaya, 2026)
Digital health platforms, including social media sites like TikTok and Facebook, have become important spaces for health communication, offering opportunities for peer support and information sharing. However, these platforms also pose significant risks, including misinformation, privacy violations, and a lack of professional oversight. This scoping review investigated the coping mechanisms used by patients and healthcare providers in digital health environments, with a focus on navigating misinformation andunregulated content on social media. A thematic analysis was conducted to identify dominant coping strategies and recurring challenges. The most common coping strategies included cross-checking health information with verified sources, avoiding unverified accounts, and seeking direct consultation with qualified professionals. Despite these strategies, users remain vulnerable due to inconsistent regulation, limited digital health literacy, and the lack of mechanisms for verifying professional credentials online. Digital health ecosystems must be supported by more robust and enforceable regulatory frameworks. Strengthening privacy protocols andissuing platform-specific guidelines for ethical conduct can further protect users and improve trust in digital health communication. This study advances understanding of coping mechanisms in digital health by synthesizing how users manage misinformation, privacy, and oversight challenges on social media, offering insights to improve safety and accountability and to inform future policy.